Solve by the substitution method 8x + 7y = 19 , -5x + y = 15

Question

Asked 10/10/2010 10:06:50 PM

Updated 10/25/2014 4:09:51 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [10/25/2014 4:09:48 PM], Confirmed by andrewpallarca [10/25/2014 4:09:51 PM]

Expert answered|dame016|Points 111|

Question

Asked 10/10/2010 10:06:50 PM

Updated 10/25/2014 4:09:51 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [10/25/2014 4:09:48 PM], Confirmed by andrewpallarca [10/25/2014 4:09:51 PM]

Rating

3

The solution for 2x + 3y = 11, -8x + y = 47 is:

x = -5, y = 7

SUBSTITUTION METHOD:

2x + 3y = 11, -8 + y = 47;

Isolate y in eq 2:

y = 8x + 47;

Put the value of y to eq. 1, and solve for x:

2x + 3(8x + 47) = 11;

2x + 24x + 141 = 11;

26x + 141 = 11;

26x = 11 - 141;

26x = -130;

x = -130/26;

x = -5;

Put x = -5 to any equation, and solve for y:

2(-5) + 3y = 11;

-10 + 3y = 11;

3y = 11 + 10;

3y = 21;

y = 21/3;

y = 7

x = -5, y = 7

SUBSTITUTION METHOD:

2x + 3y = 11, -8 + y = 47;

Isolate y in eq 2:

y = 8x + 47;

Put the value of y to eq. 1, and solve for x:

2x + 3(8x + 47) = 11;

2x + 24x + 141 = 11;

26x + 141 = 11;

26x = 11 - 141;

26x = -130;

x = -130/26;

x = -5;

Put x = -5 to any equation, and solve for y:

2(-5) + 3y = 11;

-10 + 3y = 11;

3y = 11 + 10;

3y = 21;

y = 21/3;

y = 7

Added 10/25/2014 4:08:54 PM

This answer has been confirmed as correct and helpful.

30,149,087

questions answered

There are no comments.